Lack of Change in the Projected Frequency and Persistence of Atmospheric Circulation Types Over Central Europe. Issue 9 (2nd May 2020) - Huguenin, Maurice F.; Fischer, Erich M.; Kotlarski, Sven; Scherrer, Simon C.; Schwierz, Cornelia; Knutti, Reto
Abstract: In recent summers, Europe experienced record‐breaking heatwaves, wildfires (in Northern Europe), and large‐scale water scarcity. Apart from anthropogenic warming, one contribution leading to such exceptionally hot weather was a weaker jet stream allowing a quasi‐stationary high‐pressure system to persist for many days. Here, we quantify changes in the frequency and persistence of the Central European large‐scale circulation types using various climate models. Independent of the circulation type, the models project warmer and drier future summer conditions in Central Europe, but no consistent shift to a more persistent summer or winter circulation. Most of the frequency and persistence changes are small and either within the internal variability or inconsistent across models. The model projections in this study do not support the claim of more persistent weather over Central Europe. Reconciling the results of different approaches and classifications is therefore critical to understand and predict changes in extreme weather over Europe. Plain Language Summary: The atmospheric flow over Central Europe is a key component of both its weather and climate. Recent studies have suggested that the Central European weather patterns are becoming more persistent due to our influence on the climate system. Persistent conditions can lead to record‐breaking droughts and heatwaves. It is therefore important to know how the flow conditions (also called circulation types) may change in the future. Here, we use a wide range of global climate models and classify a circulation type for each day. We distinguish between the eight main wind directions and a high‐ and low‐pressure type. Then, we quantify changes in the frequency and length of these circulation types under a strong global warming scenario at the end of the 21st century. In summer, we find a shift to warmer and drier conditions. Our models also show somewhat more persistent summer westerlies. In winter, the changes are not clear. Most of the changes in the circulation are small and likely within the range expected from natural random weather fluctuations. Our study highlights the importance of using many different climate models and other methods to investigate the highly variable Central European circulation today and under a future climate. Key Points: Climate models project warmer and drier Central European summer conditions under strong global warming independent of the circulation type For most circulation types, the models do not agree on the sign and/or magnitude of the projected change in the frequency and persistence Current global climate models do not support a general trend towards more persistent weather in Central Europe